IMPLEMENTASI PROGRAM LITERASI SEBAGAI AKTUALISASI PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Rokim Rokim (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
Learning and teaching process could be achieved through easy-to-do practical exercises and regular coaching to students. This is one of the efforts in improving the students' skills. Literacy programs are very important for students for being able to affect their learning success and life. Good literacy skills will help students in understanding oral, written, or visual texts. Therefore the development of students' literacy in learning is always conducted through such integrated activities as listening, speaking, reading and writing. On this stand, these four skills have a very close relationship, although each has its own certain characteristics. That is why, learning in a certain skill could improve the other skills. For example reading learning could also improve such skills as speaking, listening and writing. After the students read, of course the teacher will raise questions about the content of the reading and the students are asked to retell what is read with their own words. Keywords: Islamic education, literacy programs, learning and teaching process